Delineating weak zones in limestone based on borehole drilling and electrical resistivity tomography - Muhammad Jahangir Khan; Dr.SIDDIQUE AKHTAR EHSAN; Umair Bin Nisar; Shahrukh Ali Syed; Mubarik Ali; Hummad Habib Qazi; Saif ur Rehman Khan Jadoon; Sarfaraz Khan (Kuwait Journal of Science)
This study is focused on imaging of weak zones in subsurface using geophysical and geotechnical data. These weak zones are present within Jhill limestone of Miocene age across the northern, Karachi. A total of forty nine core samples were collected from eleven boreholes about 30 m deep within the study area. The core analysis reveals presence of cavities in fractured limestone at shallow and deep levels. The lateral extension and thickness of these weak zones are well imaged by the electrical resistivity tomography (ERT) dataset. The ERT dataset were acquired using POLARES 2.0 and modelled by the inversion software RES2Dinv. The 2D tomographs of the six profiles show variability in the ground resistivity response. The ERT profiles are interpreted using on hand samples collects from drilled well. These images reveal relatively high resistivity values that may represent intercalation of dry clay and marl beds within limestone. The medium resistivity values suggest presence of clay and sand in highly fractured limestone or surficial dry features. The low resistivity values are interpreted to be originated by the weak zones filled with lithologies having high moisture content within limestone. The core samples were analysed for geotechnical parameters including natural moisture content, dry density, bulk density and specific gravity. The integration of borehole and ERT datasets placed key constraints on lithology and delineated weak zones in the northern and central regions, which should be well-cemented to avoid any hazards.